The time in ruins: photographic essay - Sotolongo Menéndez, Claudio (2023)
This is a photographic essay that, faced with the deterioration of the housing stock in Centro Habana, Cuba, aims to build a typological archive of the decorations with tiles or glazed hydraulic tiles, still visible in some buildings, through documentary photography, to preserve what was once was part of the daily life of residents and passers-by, and that has been recognized by specialists as part of the city’s heritage